Principles for technology use in athlete support across the skill level continuum - McCosker, C.; Otte, F.; Rothwell, M.; Davids, K. (International Journal of Sports Science & Coaching, 2022)
A major challenge to sport practitioners working across all levels of sport is ensuring that technological platforms are integrated effectively to assist learning along the development pathway. Under the framework of ecological dynamics, we introduce technology as a support opportunity for athletes to learn to become better attuned to, and utilise, key sources of information to self-regulate their actions. Importantly, technology not only supports learning, but also serves as a tool to encourage active engagement in learning from early childhood to late adulthood. Coaches also need to be wary of the potential perils of the mismanagement of technology use and how it can act as a learning rate limiter. Misuse of technological tools may inhibit the learning process by inhibiting an athlete s ability or willingness to explore and exploit available information in the performance environment, as well as stimulate possible feelings of control and surveillance. By illustrating how technology may complement athlete learning under the guidance of the theoretical framework of ecological dynamics, it is intended that coaches may gain a better understanding of how technological tools can be used more strategically to enhance learning.